Strategies of political elites to reform the image of the legislative institution through the state press An analytical study of the statements of members of the Iraqi Council of Representatives in Al-Sabah newspaper during the crisis of the October 2019 - Al-Musawi, Haider Ghazi Hussain (The International and Political Journal, 2022)
The political elites represented by members of the Iraqi parliament seek to employ the press to pass statements in order to achieve specific goals and objectives, and among those goals is to reform the institution’s image among the public, especially during crises, and among the crises that Iraq witnessed was the crisis of the October 2019 demonstrations and the calls it included to dissolve the parliament Therefore, a number of members of the House of Representatives tried to improve and reform the parliament’s image among the public through statements made to the Iraqi press, including Al-Sabah newspaper, which is a semi-official press or a state press funded by public money. However, the statements were not based on scientific foundations approved by theories. And methodologies for repairing or restoring the image. The strategies that were used to repair the image and its techniques were spontaneous and not systematic, and what combined them with scientific theories. The final goal is to repair the image without adopting the foundations of using those strategies and techniques in the best way, which contributes to increasing doubts about the institution’s ability to overcome crises and its supervisory performance or Legislative.